Interaction between grazing by starfish (parvulastra exigua) and nutrient enrichment on intertidal soft-sediment communities. - Qwabe, Welly (Department of Biological Sciences, 2024)
Top-down and bottom-up forces are important determinants of community structure, having significant control over diversity metrics. Bottom-up control is frequently represented by nutrient level, which determines ecosystem productivity. Top-down control includes consumer (e.g. grazers and predators) effects on lower trophic levels. Consumers determine community structure through 2 main interacting mechanisms viz. by creating physical disturbances to the habitat and by removing other species through consumption. Both of these mechanisms rely predominantly on the effectiveness of the consumer in terms of exerting dominance on members of lower trophic levels or in terms of generating physical disturbances to the ecosystem as well as the type of community being affected. Today, the pervasive overharvesting of important consumers and increased nutrient loading in coastal natural habitats are globally recognised as factors requiring urgent attention. Such activities can significantly modify the interaction between top-down and bottom-up forces and the consequent effects on communities. This dissertation presents results of a field experiment investigating the interactive effects of top-down (grazing) and bottom-up (nutrients) effects on intertidal soft-sediment communities on the West coast of South Africa. The herbivorous starfish (Parvulastra exigua) was the grazer used in the study, and manipulated to generate five levels of increasing starfish densities. Slow-release fertilizer (Plantacote N: P: K) was utilized to generate three levels of increasing nutrient levels effects. The experiment was undertaken based upon three central aims, the first of which was to examine if nutrient enhancement can interact with increasing starfish densities to structure communities of producers (microalgae) and consumers (macrofauna). The second aim was to examine if the interactive effects of nutrients and starfish densities can influence the microalgal biomass (Chl a) and extracellular polymeric substances (EPS) associated with the sediment. The third aim was to investigate if the interactive effects of nutrients and starfish densities can affect functional group composition of macrofauna. The findings did not show interactive effects of nutrients and starfish on microalgal and macrofaunal community assemblages. There was, however, a strong influence of nutrient enhancement on both communities. The responses of microalgal morphotypes and macrofaunal species to nutrient enhancement were limited. Seventeen of the 59 microalgal morphotypes which dominated community structure were affected by nutrient enhancement whereas two of the six dominant macrofaunal species were affected by nutrient enhancement. These results indicate that the effects of nutrients on both communities operate on a few taxa. Microalgal morphotypes showed varying responses to increasing nutrient levels including unimodal hump and U-shapes, and linear increases and decreases. The interactive effect of nutrient enrichment and starfish densities was only apparent for few microalgal morphotypes, macrofaunal species and EPS concentration. For diversity indices, only macrofaunal species diversity was influenced by nutrients but the response pattern was not graphically obvious. At the functional group level, increasing nutrient enhancement resulted in an increase in abundance of suspension feeders. Starfish density had a significant effect on EPS concentration, with a hump-shaped response to increasing starfish densities at the first level of nutrient enrichment. Microalgal species richness and diversity were also affected by starfish densities and responded in a U-shape manner against increasing starfish densities at the first and second levels of nutrient enrichment. Surface and burrowing predators/scavengers and suspension feeders were affected by starfish densities. Suspension feeders showed a hump-shaped response against increasing starfish densities at all nutrient levels. In conclusion, the top-down force exerted by P. exigua on producers and consumers was very limited in this study and the bottom-up effect of nutrients was much more important as a structuring agent of producer and consumer assemblages. The findings of the study are evaluated against the predictions of the grazer-reversal hypothesis, which predicts a promotive effect of grazing on diversity at high nutrient levels but a negative effect on diversity at low nutrient levels.